2002
DOI: 10.1074/jbc.m205063200
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Gene Expression Analysis of Osteoclastogenesisin Vitro and Elucidation of NFAT2 as a Key Regulator

Abstract: To understand the molecular events coupling between cell proliferation and differentiation by elucidating genes essential for the process, we conducted a large scale gene expression analysis of an in vitro osteoclastogenesis system consisting of recombinant RANKL and mouse RAW264 cells. The entire process leading to the formation of tartrate resistant acid phosphatase-positive multinucleated cells takes 3 days and plates become fully covered with multinucleated cells at 4 days. Microarray probing at eight time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
299
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(320 citation statements)
references
References 60 publications
15
299
0
2
Order By: Relevance
“…9,17 The expression of this transcription factor was shown to be induced by RANKL during osteoclastogenesis. 16,17 As the TAK1-MKK6-p38 pathway positively regulated Oc differentiation, we investigated whether this MAPK signalling pathway is linked to NFATc1 induction by RANKL. BMMs were infected with TAK1-DN or the control viruses and cultured for 24 h in the presence of RANKL and NFATc1 expression was assessed by Western analyses.…”
Section: Tak1-mkk6-p38 Signalling Is Necessary For Nfatc1 Induction Fmentioning
confidence: 99%
See 1 more Smart Citation
“…9,17 The expression of this transcription factor was shown to be induced by RANKL during osteoclastogenesis. 16,17 As the TAK1-MKK6-p38 pathway positively regulated Oc differentiation, we investigated whether this MAPK signalling pathway is linked to NFATc1 induction by RANKL. BMMs were infected with TAK1-DN or the control viruses and cultured for 24 h in the presence of RANKL and NFATc1 expression was assessed by Western analyses.…”
Section: Tak1-mkk6-p38 Signalling Is Necessary For Nfatc1 Induction Fmentioning
confidence: 99%
“…Recent studies have shown that the expression of NFATc1 is induced by RANKL treatment 16,17 and NFATc1-deficient embryonic stem cell lines failed to differentiate to Ocs. 17 It has been indicated in other cell types that MAPKs are involved in the regulation of NFAT family proteins.…”
Section: Introductionmentioning
confidence: 99%
“…DNA microarray analysis DNA microarray analysis using Affymetrix GeneChip technology was performed as described previously [28]. Briefly, 10 μg of total RNA was used as a template for cDNA synthesis.…”
Section: Isolation Of Total Rnamentioning
confidence: 99%
“…The TRAF-binding domains of RANK are important for the RANK-dependent induction of NF-B and JNK (21,23). In addition, the signaling pathways via the transcription factors c-Fos and nuclear factor of activated T cells c1 (NF-ATc1) seem to be important for RANKL-induced osteoclastogenesis, as outlined in recent studies (24)(25)(26). RANKL also activates the antiapoptotic serine/ threonine kinase protein kinase B/Akt through a signaling complex involving c-Src and TRAF6, which interact with one another and with RANK after receptor engagement (27).…”
mentioning
confidence: 90%